ANALISIS POSTUR KERJA MENGGUNAKAN METODE RAPID UPPER LIMB ASSESSMENT (RULA) DI UMKM KERUPUK KEMPLANG 32 KECAMATAN BUMI WARAS BANDAR LAMPUNG - Riska Restiyani; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
This study discusses work posture analysis using the rapid upper limb assessment (RULA) method at Kerupuk Kemplang 32 Micro Small and Medium Enterprises (MSMEs), Bumi Waras District, Bandar Lampung. The purpose of this study was to determine unsafe work postures for workers, and to minimize injuries to the skeletal system and nervous system caused by repetitive movements (Cumulative Trauma Disorders), how the influence of work attitudes or postures of workers and the workplace, provide recommendations for appropriate work postures. safe based on the upper limb assessment (RULA) method. This research is a descriptive study with data analysis using the RULA method. The data collection method uses primary data in the form of worker posture data which includes upper arms, forearms, wrists, hands, neck, back and legs. The results of this study indicate that the working posture of making kemplang cracker dough is divided into two activities, namely taking sago water and making the dough, both of which have a score of 7 which indicates Action Level 4 and the roasting section of kemplang crackers has the same score, 7 indicating Action Level 4. From these data, it can be concluded that this work posture needs to be improved in the near future.